Fragment Enrichment of Circulating Tumor DNA With Low-Frequency Mutations - Liu, Xiaojun; Lang, Jidong; Li, Shijun; Wang, Yuehua; Peng, Lihong; Wang, Weitao; Han, Yingmin; Qi, Cuixiao; Song, Lei; Yang, Shuangshuang; Zhang, Kaixin; Zang, Guoliang; et al. (Frontiers in Genetics, 2020)
Human blood contains cell-free DNA (cfDNA), with circulating tumor-derived DNAs (ctDNAs) widely used in cancer diagnosis and treatment. However, it is still difficult to efficiently and accurately identify and distinguish specific ctDNAs from normal cfDNA in cancer patient blood samples. In this study, ctDNA fragment length distribution analysis showed that ctDNA fragments are frequently shorter than the normal cfDNAs, which is consistent with previous findings. Interestingly, the ctDNA fragment length was found to be partially associated with the mutant allele frequency, with a low mutant allele frequency (< 0.6%) associated with a longer ctDNA fragment length when compared to normal cfDNAs. The findings of this study contribute to improving the detection of low-frequency tumor mutations.